2015
DOI: 10.36311/1981-1640.2015.v9n1.03.p22
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and structure of "Sustainable development"

Abstract: Sustainable development is an interdisciplinary subject that has developed dramatically over the last few decades. Bibliometrics offers quantitative analytical techniques with which to study the development and growth of research in this area. The information used for the present study was retrieved from the SCI-EXPANDED, SSCI, and A&HCI (Thomson Reuters) databases. The search was made on the topic "Sustainable development", limited to Document Types (Article) and Time Span (1900-2013). The result was a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Scientometric studies offer a powerful tool to generate global pictures of the research activities in a given area. There are different scientometric studies that previously analyzed sustainability, sustainable development or sustainability science based on a keyword search (Nučič, 2012;Schoolman et al, 2012;Hassan et al, 2014;Kajikawa et al, 2014;Pulgarin et al, 2015;Ramírez Ríos et al, 2016;Olawumi and Chan, 2018). Some studies focused on analyzing the output of sustainability in higher education (Bizerril et al, 2018;Veiga Ávila et al, 2018;Alejandro-Cruz et al, 2019;Hallinger and Chatpinyakoop, 2019).…”
Section: Scientometric Analyses Of Sdgs-related Research Outputs Frommentioning
confidence: 99%
See 1 more Smart Citation
“…Scientometric studies offer a powerful tool to generate global pictures of the research activities in a given area. There are different scientometric studies that previously analyzed sustainability, sustainable development or sustainability science based on a keyword search (Nučič, 2012;Schoolman et al, 2012;Hassan et al, 2014;Kajikawa et al, 2014;Pulgarin et al, 2015;Ramírez Ríos et al, 2016;Olawumi and Chan, 2018). Some studies focused on analyzing the output of sustainability in higher education (Bizerril et al, 2018;Veiga Ávila et al, 2018;Alejandro-Cruz et al, 2019;Hallinger and Chatpinyakoop, 2019).…”
Section: Scientometric Analyses Of Sdgs-related Research Outputs Frommentioning
confidence: 99%
“…There have also been previous publications discussing the growth of the scientific production related with sustainability. For example, Pulgarin et al (2015) argued that the growth of research production in sustainability can be explained by "the impact of human activity on the environment" which "is leading to this area of research [sustainability] being studied from ever more different fields." Olawumi and Chan (2018) consider that this increase could be also linked to "more efforts and resources" being devoted to this topic.…”
Section: How Has Mandsdgs Research Carried Out By Heis Developed Over Tmentioning
confidence: 99%
“…In these theories, the way in which the problem of development is perceived has changed, taking into consideration the areas being of a non-economic character (especially social issues). Pulgarín, Eklund, Garrote, & Escalona-Fernández, 2015;Bettencourt & Kaur, 2011;Cairns & Martinet, 2014;Dahl, 2012). Instead, they try to present the essence of sustainable development in the context of the issues connected with creating values in organisations, showing the mechanisms of changes at the same time and presenting their own proposals connected with the discussed topics.…”
Section: Literature Review and Theory Development Sustainable Developmentioning
confidence: 99%
“…Thus, although major references on sustainability(Hassan, Haddawy, & Zhu, 2014;Wichaisri & Sopadang, 2018) does not seem pivotal to this body of literature on social impact, there is a clear link between social impact research and the sustainable development field. Other studies have also observed a rapid growth in the number of sustainable development studies towards the end of '90s(Pulgarín, Eklund, Garrote, & Escalona-Fernández, 2015;Zhu & Hua, 2017). Further on, the most productive journals on the theme social impact declare their interdisciplinary nature and their integrative interest in themes such as environment, society, health, urban planning, among others.…”
mentioning
confidence: 99%